Groundwater and geothermal anomalies due to a prolate spheroid - HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2009)
We present an exact analytical solution of the two potential problems which can help to understand heat ﬂow and groundwater ﬂow in some deep elongated geother- mal resources. The thermal conductivity and diﬀusivity coeﬃcients of the spheroid and surrounding medium are diﬀerent. The solutions are expressed in terms of the spherical functions of the ﬁrst and second kinds. The results of numerical calculations are presented for the half-spheroidal body at the surface of the Earth.